DIE „SCHWARZEN HEFTE“: IHRE REZEPTION, IHR EINFLUSS AUF DIE WIRKUNGSGESCHICHTE DES DENKENS MARTIN HEIDEGGERS UND IHRE SACHGEMÄßE AUSLEGUNGSWEISE - Rosa Maria MARAFIOTI (Studia Universitatis Babeș-Bolyai. Philosophia)
The Black Notebooks: Their Reception, Their Influence on the “History of Effects” of Martin Heidegger’s Thought and the Appropriate Way of Interpretation. A few months before their publication in 2014, the first Martin Heidegger’s Black Notebooks already introduced a new phase of the debate about Heidegger’s supposed National Socialism and Antisemitism, since they contain questionable references to Jewish people. As of yet, most of the interpretations come down to five theses. Whilst several interpreters assert that the whole Heideggerian thought is anti-Semitic, others refer this "accusation" to a brief period in Heidegger’s life or rather attribute to this thinker an anti-Judaism inherited from the Christian tradition. Some scholars classify Heidegger’s sentences as a general critique of civilisation, whereas others pretend that the Heideggerian philosophical thought was untouched by whichever issues related to politics and race. Ascertaining the flaws in the approach of many interpreters of Heidegger’s Black Notebooks, the necessity of reading them by means of the hermeneutical method in order to reach an appropriate contextualisation is to be stressed. Only in this way can the various themes of the Notebooks be unveiled, as well as the limits and the magnitude of the Heideggerian thought.